2013
DOI: 10.1007/s00404-013-2885-x
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus among HIV-infected women with normal cervical cytology: a pilot study in Jos, Nigeria

Abstract: The prevalence of HR-HPV is seemingly high among HIV-infected women with NCC in our clinical setting. These data provide support for further investigation of the clinical implications of positive HR-HPV among HIV-infected women with NCC report in cervical cancer prevention programs in Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Kreitchmann et al (2013) studied 898 women living with HIV infection and reported that age less than 30 years was significantly associated with increased risk of abnormal cervical cytology among the women. This was similar to the account of Musa et al (2013) in Jos Nigeria who reported that age less than 30 years was significantly associated with the presence of high risk HPV DNA.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Kreitchmann et al (2013) studied 898 women living with HIV infection and reported that age less than 30 years was significantly associated with increased risk of abnormal cervical cytology among the women. This was similar to the account of Musa et al (2013) in Jos Nigeria who reported that age less than 30 years was significantly associated with the presence of high risk HPV DNA.…”
Section: Introductionsupporting
confidence: 89%
“…This association with a younger age had been reported by Musa et al (2013) in Jos Nigeria, Kreitchman et al (2013) and Koffi et al (2010) in Central African Republic. This association may be derived from a more aggressive sexual activity by the younger women, as HPV infection which is the precursor for the premalignant lesions is a sexually transmitted infection.…”
Section: Discussionsupporting
confidence: 68%
“…HPV prevalence in HIV-infected populations is more than three times the estimated prevalence of 12% found in the general population and ranges from about 31% to 57%, with higher percentages in Africa than in North America or Western Europe (185). A pilot study conducted in Jos, Nigeria, evaluated a cohort of 97 HIV-infected women age 21 to 49 with normal cytology (186). High-risk HPV was detected by the Digene HC2 assay in almost half (44.9%) of the cohort, with a significant number of the positive patients being less than 30 years of age, and most were on successful antiretroviral therapy.…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 99%
“…To assess the possible role of HR-HPV DNA testing in detecting underlying high-grade cervical lesions in women with prior NCC in the setting of HIV infection, we conducted a pilot study of HR-HPV DNA testing in women with NCC in a cohort of HIV infected women in Jos, Nigeria. The prevalence and epidemiologic factors associated with HR-HPV in our patient population have been previously reported [ 17 ]. The current report focused on colposcopic examination findings and cervical abnormalities in women with or without HR-HPV in our cohort.…”
Section: Introductionmentioning
confidence: 98%